Efecto de la congelación y la fritura en el contenido de ácidos grasos: (alfalinolenico, eicosapentaenoico y docosahexaenoico) en la especie jurel (caranx hippos) (2019)
ABSTRACT: The inclusion of polyunsaturated fatty acids (PUFA) w3, w6 and Docosahexaenoic precursors (DHA), Eicosapentaenoic (EPA), Arachidonic (AA), in the foods is important due to their cardioprotective, anti-inflammatory and anticoagulant effects. Therefore, it is important to look for food sources with these nutrients in marine species and the best way to conserve them. The objective of this study was to quantify the PUFAs of the horse mackerel fish (Caranx hippos) and evaluate the effect of freezing and frying on these. A cross-sectional study was conducted in the Gulf of Urabá (Colombia), where the AG content was analyzed in fresh, frozen (-20oC) and fried fish in canola, palm and sunflower oil. The analysis showed that the ALA, EPA and DHA of the w3 family, the ARA and the Eicosatrienoic of the w6 family decreased during freezing storage time (day 0-15-30-45-60), but did not show significant differences (p > 0,05). Regarding the frying process, a significant increase in saturated fat (p = 0,005) was found with palm oil and a significant increase in MUFAs and PUFAs with sunflower and canola oil (p = 0,0005). Therefore, it can be concluded that freezing of the horse mackerel did not show a decrease in the PUFA profile, while during the frying process there were changes in the AG content. The best oil for frying the horse mackerel is Canola, because its ALA content improves the w3 / w6 ratio in fish.